2007
DOI: 10.1194/jlr.m600167-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Age-related impairment of HDL-mediated cholesterol efflux

Abstract: Our aim in this study was to investigate the effect of aging on the capacity of HDLs to promote reverse cholesterol transport. HDLs were isolated from plasma of young (Y-HDL) and elderly (E-HDL) subjects. HDL-mediated cholesterol efflux was studied using THP-1 and J774 macrophages. Our results show that E-HDLs present a lower capacity to promote cholesterol efflux than Y-HDLs (41.7 6 1.4% vs. 49.0 6 2.2%, respectively; P 5 0.013). Reduction in the HDL-mediated cholesterol efflux capacity with aging was more si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 45 publications
6
51
1
1
Order By: Relevance
“…While T cells from young subjects recovered membrane fluidity after 24h, T cells from elderly subjects exhibited fluctuations in membrane fluidity over the time course tested here. These data confirmed that HDL from elderly subjects are unable to support efficient cholesterol efflux (Berrougui et al 2007) and may contribute to functional alterations in the T cell membrane.…”
Section: High Membrane Cholesterol Content Is Associated With Alteredsupporting
confidence: 74%
“…While T cells from young subjects recovered membrane fluidity after 24h, T cells from elderly subjects exhibited fluctuations in membrane fluidity over the time course tested here. These data confirmed that HDL from elderly subjects are unable to support efficient cholesterol efflux (Berrougui et al 2007) and may contribute to functional alterations in the T cell membrane.…”
Section: High Membrane Cholesterol Content Is Associated With Alteredsupporting
confidence: 74%
“…27 Age-dependent reductions in LPL or LCAT activity and HDL particle size are possible reasons. These alterations, however, greatly vary and seem to have a strong genetic background.…”
Section: Influence Of Age On Hdl Particlementioning
confidence: 99%
“…26 The activity of enzymes involved in HDL formation and conversion of HDL subclasses may change as persons age. 27,30 Moreover, most of the HDL signaling pathways 40 -50 are potentially compromised in aged cells. 24 -26 For example, cdc42 activity is reduced in senescent cells and may contribute to impairement of lipid transport in Werner syndrome.…”
Section: Other Cell and Plasma Proteins Involved In Cholesterol Homeomentioning
confidence: 99%
“…The properties of HDL particles, the levels of HDL-C and the genetic contribution to HDL-C change with age [89,90 ]. For example, in a longitudinal study [89], the APOE isoform polymorphism influenced HDL-C in an age-dependent manner.…”
Section: Hdl-c Level Is An Emergent Property Of a Dynamic Systemmentioning
confidence: 98%